Kematangan Etika Pada Pendidikan Akuntansi : Tinjauan After Virtue - Mujtaba, Muhammad Irsyad Elfin; Prestiani, Tri Sangga (Owner : Riset dan Jurnal Akuntansi, 2024)
The accounting scandals that have occurred so far are thought to be the result of ethical failures and the role of accounting education has been asked to be responsible for them. However, the ethical maturity of accounting students during their educational process is still questionable. The influence of mainstream Anglo-American capitalist culture is the cause. To address this, Alasdair MacIntyre's After Virtue moral discourse is proposed with the main focus being to answer the question "what kind of person do I want to be?" This research uses a library research approach by reviewing literature that discusses ethics, accounting education, and after virtue. The analysis technique used is descriptive including interpretation, analysis and understanding of the literature that has been collected. The data that has been collected is analyzed in three stages, namely data reduction, data presentation, and drawing conclusions. This paper argues that ethical maturity achieved through education will not only emphasize moral reasoning in accounting students but also the ability to act ethically. Apart from that, the role of wisdom that contains ethical values also strengthens this. The After Virtue discourse will lead to ethical maturity by developing moral behavior through intellectual excellence and character excellence during the educational process.